Putting the Parts Together : Trade, Vertical Linkages, and Business Cycle Comovement - Levchenko, Andrei; Di Giovanni, Julian (Washington, D.C. : International Monetary Fund, 2009)
Countries that trade more with each other exhibit higher business cycle correlation. This paper examines the mechanisms underlying this relationship using a large cross-country industry-level panel dataset of manufacturing production and trade. We show that sector pairs that experience more bilateral trade exhibit stronger comovement. Vertical linkages in production are an important explanation behind this effect: bilateral international trade increases comovement significantly more in cross-border industry pairs that use each other as intermediate inputs. Our estimates imply that these vertical production linkages account for some 30% of the total impact of bilateral trade on the business cycle correlation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet